FACTORS INFLUENCING THE DEGREE OF ERECTILE DYSFUNCTION IN BICYCLE RACE ATHLETES - Tampubolon, Daniel Taruna; Wibisono, Dimas Sindhu; Muttaqin, Zainal; Julianti, Hari Peni (Indonesian Urological Association, 2021)
Objective: This research aims to identify factors influencing the degree of erectile dysfunction in bicycle racing athletes. Material & Methods: This study used quantitative analysis and cross-sectional research design. Samples included in this research were 54 respondents in accordance to the inclusion and exclusion criteria of this study, and were willing to participate in this research. The data were collected using the IIEF-5 (International Index of Erectile Function-5) questionnaire. The data were then edited, coded and analyzed using Chi-square (bivariate analysis). Results: The results showed correlations between the degree of erectile dysfunction in bicycle race athletes and age (PR= 1.182; 95%CI= 0.403-3.465; p= 0.976), cycling history (PR= 0.462; 95% CI= 0.490-4363; p= 0.687), cycling frequency (PR=1.400; 95% CI= 0.299-6.560; p= 0.72), cycling duration (PR= 0.333; 95% CI= 0.074-1.507; p= 0.165), furthest cycling distance (PR= 0.883; 95% CI= 0.267-2.919; p= 1.00), and type of saddle (PR= 0.271; 95% CI= 0.481-1.547; p= 0.221) respectively. Conclusion: There were no significant correlation (p= >0.05) in all variables analyzed in this study.